EKSPRESI Nuclear Factor of Activated T cells c-1 (NFATc-1) DAN OSTEOKALSIN PADA KERUSAKAN TULANG PERIAPIKAL AKIBAT INDUKSI BAKTERI Enterococcus faecalis - Arindah Hadi; M. Roelianto; Ari Subiyanto; Tamara Yuanita (Universitas Airlangga, 2017)
Background. The main etiology of endodontic treatment failure is caused by bacteries that stay in the root canal. E.faecalis is a bactery that is found as an etiology of endodontic treatment failure. Cell wall of this bacteria is containing Lipoteichoic acid (LTA). LTA can penetrate into the periradicular tissue, act as endotoxin in host and cause periradicular inflammation then lead to bone destruction. Bone destruction occurs due to the inflammation process that is mediated by immune system. The important cell in the process of bone destruction is osteoclast. Bone destruction is marked by the form of osteoclast that is called osteoclastogenesis. NFATc-1 and osteocalcin play important things in osteoclastogenesis. Purpose. The aim of this study is to know about the expression of NFATc-1 and osteocalcin during the periapical bone destruction due to induction of E.faecalis. Method. This study used laboratory experimental with the post test only control group design. A total of 54 male rats were randomly divided into 2 main groups, which each main group had 3 subgroups. Group A (control) : every tooth was induced only by sterile BHIb. Group A had 3 subgroups (A Control day 3, 10, and 21), group B : every tooth was induced by 10 μl BHI-b E.faecalis ATCC212(106 CFU), it was contained 3 sub groups (B day 3,10, and 21). The animals were sacrificed based on their days scheduled group and prepared for histological examination of periapical bone, then we did the immunohistochemistry followed by calculation on the light microscope. Result. The analysis revealed that the expression of NFATc-1 and osteoclast increased significantly in group B when E.faecalis was induced. Conclusion. From this study we know that the expression of NFATc-1 and osteocalcin are increasing during the periapical bone destruction that induced by E.faecalis.